Factors Influencing the Health-Seeking Behavior of the Street Children in Indonesia - Chairani, Reni; Aryani, Ratna; Lestari, Tri Riana; Dinarti; Nurhaeni, Heni (International Journal of Allied Medical Sciences and Clinical Research, 2021)
Background Assessing the health-seeking behaviour is a key aspect for planning healthcare programmes. Yet, this aspect remains understudied in the street children population in Indonesia. Objective To identify the social factors that affect the health-seeking behaviour of the children-on-the-street aged 15-20 years in urban areas in Indonesia. Method This study used a cross-sectional design. A total of 115 street children were recruited by using simple random sampling method in five shelters in different cities of Indonesia. Data were analysed with descriptive analysis, cross tabulation with ?2 Yates corrections, and double logistic regression Results Family support was the strongest factor affecting the health-seeking behaviour of the street adolescents (OR = 4.926). Conclusion The results show that strengthening family functioning could be an effective strategy to improve the health outcomes of the street adolescents in the large urban cities of Indonesia.